Bedside assessment of ophthalmic manifestations in neurocritical care: A study in Southern India - Chethana Warad; Shrusty Mohapatra; Abhyudaya Mehta (Indian Journal of Ophthalmology, 2024)
Purpose: This study aimed to investigate the incidence of Ocular Surface Disorders (OSDs), including Dry Eye Disease, Chemosis, and Exposure Keratitis, among patients admitted to the Neurocritical Care Unit (NCC). Additionally, we sought to assess the correlation between these OSDs, the length of hospitalization at NCC, and the Glasgow Coma Score (GCS). The heightened risk of OSD development in the NCC environment, coupled with pre-existing neurological impairments, can lead to conditions like dry eye disease, chemosis, corneal abrasions, and infectious keratitis, ultimately resulting in corneal opacities and perforations that significantly impact visual acuity and overall quality of life. Methods: In this observational cross-sectional study, we examined the ocular health of all patients admitted to an NCC unit from February to May 2022. We assessed the presence of Conjunctivitis, chemosis, Keratitis, and Dry Eyes in relation to the duration of stay at NCC, GCS, lagophthalmos, adherence to the prescribed eye care protocol in NCC, and the use of mechanical ventilation. Our study comprised one hundred subjects over a four-month period, with a mean age of 51.92 ± 18.73 years (ranging from 17 to 89), including 70% males and 30% females (gender ratio of 2.33). Results: Our findings revealed that 26 eyes (13%) exhibited Conjunctival Hyperemia, 23 eyes (11.5%) displayed Chemosis, and severe dry eye was prevalent in 41 (20.5%) eyes. A statistically significant association was observed between GCS (p-value <0.001) and Keratitis (p-value 0.0035) with dry eyes (Chi-Square Test). Notably, the incidence of dry eyes was significantly higher among patients with a prolonged stay of ≥10 days (p-value 0.003). Conclusions: Patients admitted to Neurocritical Care Units necessitate meticulous eye care and structured protocols to mitigate the risk of long-term ocular complications such as exposure keratitis. Given their heightened susceptibility to these conditions, proactive measures are imperative to ensure optimal ocular health among NCC patients.